Th2 cell-intrinsic hypo-responsiveness determines susceptibility to helminth infection. - Nienke van der Werf; Stephen A Redpath; Miyuki Azuma; Hideo Yagita; Matthew D Taylor (PLoS Pathogens)
The suppression of protective Type 2 immunity is a principal factor driving the chronicity of helminth infections, and has been attributed to a range of Th2 cell-extrinsic immune-regulators. However, the intrinsic fate of parasite-specific Th2 cells within a chronic immune down-regulatory environment, and the resultant impact such fate changes may have on host resistance is unknown. We used IL-4gfp reporter mice to demonstrate that during chronic helminth infection with the filarial nematode Litomosoides sigmodontis, CD4(+) Th2 cells are conditioned towards an intrinsically hypo-responsive phenotype, characterised by a loss of functional ability to proliferate and produce the cytokines IL-4, IL-5 and IL-2. Th2 cell hypo-responsiveness was a key element determining susceptibility to L. sigmodontis infection, and could be reversed in vivo by blockade of PD-1 resulting in long-term recovery of Th2 cell functional quality and enhanced resistance. Contrasting with T cell dysfunction in Type 1 settings, the control of Th2 cell hypo-responsiveness by PD-1 was mediated through PD-L2, and not PD-L1. Thus, intrinsic changes in Th2 cell quality leading to a functionally hypo-responsive phenotype play a key role in determining susceptibility to filarial infection, and the therapeutic manipulation of Th2 cell-intrinsic quality provides a potential avenue for promoting resistance to helminths.